A survey of demolition works in Malaysia - Masalamy @ Navaratnam, Visvan (2005)
As Malaysia continues to progress towards achieving a developed status, shortage of land and space will require existing structures to be demolished, in order to make way for new development. The dilemma of insufficient land in urban areas to sustain growth and cater for increasing modernization demands will augment to a critical level. Therefore, there is dire need to expedite research in the field of demolition works within the country. This research was aimed at developing an overview as well as assessing the potential of demolition operations in Malaysia. Two varying methodologies were adopted comprising a case study and a questionnaire survey. The former looked into the Lumba Kuda Flats demolition operations which formed part of the Gerbang Selatan Bersepadu project. On the other hand, the latter targeted feedback from the local industry’s professionals. The case study revealed that local contractors were capable of managing large scaled demolition projects in terms of project planning, demolition techniques, health and safety implementation as well as environmental management. All work aspects met the requirements of international standards and codes and complied with local legislation. The survey reported beneficial data which provided strong indication of the industry’s capabilities and identified problems plaguing the various aspects of demolition operations. In order to overcome the limitations and barriers presently faced, local professionals needed to look beyond and consider what the global demolition market had to offer. Apart from that, active government participation was extremely necessary in certain areas to provide long term and effective solutions. The benefits offered by the research are invaluable as it serves as a strong foundation and reference for developing future specifications, standards and legislation to govern demolition operations.